2019
DOI: 10.1111/mmi.14199
|View full text |Cite
|
Sign up to set email alerts
|

Differential modes of crosslinking establish spatially distinct regions of peptidoglycan in Caulobacter crescentus

Abstract: Summary The diversity of cell shapes across the bacterial kingdom reflects evolutionary pressures that have produced physiologically important morphologies. While efforts have been made to understand the regulation of some prototypical cell morphologies such as that of rod‐shaped Escherichia coli, little is known about most cell shapes. For Caulobacter crescentus, polar stalk synthesis is tied to its dimorphic life cycle, and stalk elongation is regulated by phosphate availability. Based on the previous observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 56 publications
(77 reference statements)
0
23
0
Order By: Relevance
“…In fact, there is a certain correlation between the amount of LD-cross-linkage and sensitivity to lysozyme in other Gram-negative bacteria as well. For instance, A. tumefaciens has a PG rich in LD-cross-links and is also highly resistant to lysozyme degradation [75]. In E. coli, the lower susceptibility to…”
Section: Ld-cross-links Might Provide Lysozyme Resistancementioning
confidence: 99%
“…In fact, there is a certain correlation between the amount of LD-cross-linkage and sensitivity to lysozyme in other Gram-negative bacteria as well. For instance, A. tumefaciens has a PG rich in LD-cross-links and is also highly resistant to lysozyme degradation [75]. In E. coli, the lower susceptibility to…”
Section: Ld-cross-links Might Provide Lysozyme Resistancementioning
confidence: 99%
“…Upregulation of PG-modifying enzymes may serve to reinforce the envelope during stress in other compartments of the envelope so as to increase its overall stability. Interestingly, it was recently shown that increased levels of DAP-DAP crosslinkages increases resistance to lysozyme (Stankeviciute et al, 2019). It is possible that Cpx-regulation of ldtD and ygaU may be a strategy for dealing with envelope stress arising from host innate immunity.…”
Section: The Cpxra Two-component Systemmentioning
confidence: 99%
“…In contrast to the PG transglycosylases, inhibition of the transpeptidase PBP2 blocks stalk elongation (9,10), as does depletion of MreB or RodA (11), which are regulators of PBP2 activity in E. coli (12,13). Additionally, the stalk PG is enriched for LD-cross-links (between meso-DAP residues on neighboring peptide stems) (9,14); while these LD-cross-links increase stalk PG resistance to lysozyme-mediated degradation (14), abrogation of LD-transpeptidation has no effect on stalk elongation (9,14).…”
mentioning
confidence: 99%